Synopsis of Euphorbia (Euphorbiaceae) in the state of São Paulo, Brazil - Silva, Otávio Luis Marques Da; Cordeiro, Inês; Caruzo, Maria Beatriz Rossi (Phytotaxa, 2014)
Euphorbia is the largest genus of Euphorbiaceae and is among the giant genera of Angiosperms. In the state of São Paulo, the genus is represented by 23 species occurring in savannas, high altitude fields, and anthropic areas. This work includes an identification key, photographs, and comments on morphology, habitat, and geographical distribution. We reestablish Euphorbia chrysophylla and recognize Leptopus brasiliensis as a synonym of Euphorbia sciadophila. Six new records for the state of São Paulo are presented: Euphorbia adenoptera, E. bahiensis, E. chrysophylla, E. cordeiroae, E. foliolosa and E. ophthalmica. Eight lectotypes are designated.